Stent graft placement for traumatic lumbar artery injury in which coil embolization is not feasible - Koji Miura; Tatsuhiko Komiya; Susumu Matsushime; Naoki Oka; Keisuke Kamo (Trauma Case Reports, 2023)
Lumber artery injuries are anatomically difficult to treat surgically, and coil embolization is a first-line treatment option for them. In some cases, however, there is not enough space for coil embolization, for which stent graft placement can be an alternative therapy. We report a case of traumatic lumbar artery injury in which stent graft placement was performed due to lack of space for coil embolization.